RANCANG BANGUN SISTEM INFORMASI â€œGO-SIPâ€ BERBASIS WEB DI DINAS LINGKUNGAN HIDUP KABUPATEN SUMBAWA - Ali Kafabillah Assegaf , Ridwan; Suarantalla, Ryan; Herfandi (Jurnal TAMBORA, 2021)
With the advancement of information technology, the need for accurate information is very highneeded, because information will be an important element incurrent and future development of society. Garbage isconsequences of human activities are so diverse. Amount or volume of wastedirectly proportional to the level of consumption of goods that we use everyday.Handling waste with the old system still causes various problems plusThe increasing population growth results in the amount of wastethe output is also great. The purpose of this thesis research is to analyze the systemwaste management at the Sumbawa district environmental office, designingan information system to address the waste problem in Sumbawa district, anddesigning a Go-SIP (government samawa clean garbage) information system in the districtSumbawa. The final result of this thesis research is the "Go-SIP" Information SystemBased on the website of the Sumbawa Regency Environmental Service, which can helpthe community and staff at the Environmental Service to be able to complete their dutiesaccurately.